A Lip Repositioning Technique Using Polyester Threads for Gummy Smile Treatment - Renata Oliveira Ribeiro Horn; Carlos Nelson Elias; Júlio César Joly (International Journal of Dentistry)
A new technique is proposed in this study to correct the gummy smile (GS) with myotomy, combining lip repositioning with the insertion of polyester threads at the surgical site to act as a physical barrier and control relapse. 11 patients were clinically assessed (30.2 ± 7.43 years old, 90.9% females and 9.10% males). All patients presented gingival display (GD) greater than 4 mm. Hypermobile upper lip (HUL), vertical maxillary excess (VME) + HUL, altered passive eruption (APE) + HUL, and VME + APE were the etiologies identified. Three polyester threads were inserted in each patient one month after the surgery. The GS was measured before, 6 months, and 12 months after the surgery. The results showed a reduction in the mean GD of the patients, 4.42 mm after 6 months (p value = 0.000) and 4.13 mm after 12 months (p value = 0.000). The largest relapse was 0.29 mm and was not statistically significant (p value = 0.07). The Friedman test with pairwise comparisons was used to determine the existence of statistically significant differences in GD between the periods analyzed. The results showed that the proposed technique was successful in treating GS, presenting significant reductions in the GD 12 months after surgery and controlling the relapse.